Pengembangan Web Alofisika Sebagai Sumber Belajar Mandiri Untuk SMA/MA Kelas X Pada Pokok Bahasan Momentum dan Impuls - Riza Hayyuningtias; Joko Purwanto (Universitas Sebelas Maret, 2019)
Abstract: This research aims to design a quality of alophysics web as a source of independent learning for Senior High School Class X based on expert judgment and student responses. The research belongs to Research and Development (R&D). This development is done using Plomp research model which includes 5 steps, namely (1) Prelimenary Investigation (2) Design (3) Realization/Construction (4) Evaluation and Revision (5) Implementation. These research instruments are validation sheet, Alophysics web quality assessment sheet, student response sheet. The quality of Alophysics web used 4 Likert scale and student response used Guttman scale, both are in checklist forms. The final result of this study is the web of Alophysics as a source of independent learning for Senior High School Class X on the subject of momentum and impulses. The quality of the web of Alophysics based on expert material assessment obtained a mean score of 3.2 with good category (B), media expert judgment obtained an average score of 2.9 with good category (B), and the physics teacher assessment obtained a mean score of 3.83 with the very good category (SB). At the implementation stage produces the responses of students agree (S) with a mean score of 1.00 in limited trials and 0.95 in broad trials.Abstrak: Penelitian ini bertujuan untuk mendesain web alofisika yang berkualitas sebagai sumber belajar mandiri untuk SMA/MA Kelas X berdasarkan penilaian ahli dan respon peserta didik. Penelitian ini merupakan penelitian Research and Development (R&D). Pengembangan dilakukan dengan menggunakan model penelitian Plomp yang meliputi 5 langkah yaitu (1) Prelimenary Investigation (2) Design (3) Realization/Construction (4) Evaluation and Revision (5) Implementation. Instrumen penelitian berupa lembar validasi, lembar penilaian kualitas web alofisika, dan lembar respon peserta didik. Penilaian kualitas web alofisika menggunakan skala Likert dengan skala 4 dan respon peserta didik menggunakan Guttman yang dibuat dalam bentuk checklist. Hasil akhir penelitian ini adalah web alofisika sebagai sumber belajar mandiri untuk SMA/MA Kelas X pada pokok bahasan momentum dan impuls. Kualitas web alofisika berdasarkan penilaian ahli materi diperoleh rerata skor 3,2 dengan kategori baik (B), penilaian ahli media diperoleh rerata skor 2,9 dengan kategori baik (B), dan penilaian guru fisika diperoleh rerata skor 3,83 dengan kategori sangat baik (SB). Pada tahap implementasi menghasilkan respon peserta didik setuju (S) dengan rerata skor 1,00 pada uji coba terbatas dan 0,95 pada uji coba luas.